Model Pengembangan Pembelajaran PAI di Sekolah Melalui Berbagai Pendekatan - Sigit Tri Utomo (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2017)
Abstract:The learning of Islamic education today is at the heart of the character formation of learners. Because true education changes the way people view from bad to good, from being unable to be from unable to be able. With PAI learning model in School through various approaches expected education process in effort of character formation can be optimal. This research is a qualitative research using library approach, which is an approach that examines and uses literature as reference and reference in managing data. In this case the object is the model of PAI learning development in schools through various approaches.Methods of data collection in this study using literature study. In this stage, the researcher seeks to select the data (books) that have relevance to the model of PAI learning development in schools through various approaches. Then the author also uses synthesis analysis that is with the handling of certain scientific objects by combining the meaning of one with another understanding, which ultimately can be obtained new knowledge that is the urgency of the library as an effort to reduce the behavior of students' deviations in school. The author also uses content analysis that is research conducted on the information documented in the recording, good pictures, sounds, writings and others. With this method will be done data analysis and processing scientifically about the contents of the writing model of learning development of PAI in schools through various approaches.The results showed that in the development of learning PAI there are several models such as Faith Approach, Approach Experiences, Approach Habituation, Rational Approach, Emotional Approach, Functional Approach, Exemplary Approach, and others.